PRODUKSI TEPUNG UBI JALAR UNGU DENGAN PROSES BLANCHING UNTUK MENJAGA STABILITAS SENYAWA FUNGSIONALNYA - Laga, Amran; Budyghifari, Laras; K. Sukendar, Nandi; Syarifuddin, Adiansyah (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2020)
ABSTRACTPurple sweet potato as a potential food source, apart from being a source of calories, also has various functional compounds that play an important role in health aspects. Purple sweet potato has bioactive compounds such as beta-carotene, vitamin A, anthocyanins, and phenolic compounds that work together to determine antioxidant activity. In this study, a blanching technique was used before the drying process to minimize the damage to bioactive compounds due to enzymatic activity during processing. The slices of sweet potato were blanched using the steaming method and boiled in boiling water. Then, they were dried at 60 oC for 16 hours with sampling every four hours. The results obtained by the drying process of purple sweet potato flour with and without blanching show that the optimal drying time was achieved at 8 hours with a moisture content of 7.49%. Blanching treatment in the process of making purple sweet potato flour gave significant anthocyanin levels, which were 1.43 mg/g (boiled blanching) and 1.19 mg/g (steamed blanching), while the without blanching treatment had an anthocyanin level of 0.57 mg/g. The drying process of purple sweet potato flour which begins with the blanching process can increase or stabilize the anthocyanin levels and the brightness of the flour, but the antioxidant activity becomes very weak at 8-16 hours of drying. The blanching process with the boiled method resulted in very weak antioxidant activity (IC50 290.39 ppm) compared to steamed blanching with IC50 activity of 187.05 ppm (weak).Keywords: sweet potato, blanching, flour, anthocyanin, antioxidants.ABSTRAKUbi jalar ungu sebagai salah satu sumber pangan potensial, selain sebagai sumber kalori juga memiliki berbagai senyawa fungsional yang mempunyai peranan penting dalam aspek kesehatan. Ubi jalar ungu memiliki senyawa bioaktif seperti beta-karoten, vitamin A, antosianin dan senyawa fenol yang bersinergi dalam menentukan aktivitas antioksidan. Pada penelitian ini dilakuakn teknik blanching sebelum proses pengeringan untuk meminimalkan kerusakan senyawa bioaktif akibat aktivitas enzimatik selama pengolahan. Irisan ubi diblanching dengan metode kukus dan rebus dalam air mendidih. Selanjutnya dikeringkan pada suhu 60 oC selama 16 jam dengan pengambilan sampel setiap empat jam. Hasil yang diperoleh proses pengeringan tepung ubi jalar ungu baik dengan perlakuan blanching maupun tanpa blanching optimal tercapai pada lama pengeringan 8 jam dengan kadar air 7,49 %. Perlakuan blanching pada proses pembuatan tepung ubi jalar ungu memberikan hasil kadar antosianin yang signifikan yakni 1,43 mg/g (blanching rebus) dan 1,19 mg/g (blanching kukus), sedangkan perlakuan tanpa blanching 0,57 mg/g. Pengeringan tepung ubi jalar ungu yang diawali dengan proses blanching dapat meningkatkan atau menstabilkan kadar antosianin dan kecerahan warna tepung , tetapi aktivitas antioksidan menjadi